To ventilate or not to ventilate during bystander CPR — A EuReCa TWO analysis. (September 2021) - Wnent, Jan; Tjelmeland, Ingvild; Lefering, Rolf; Koster, Rudolph W.; Maurer, Holger; Masterson, Siobhán; Herlitz, Johan; Böttiger, Bernd W.; Ortiz, Fernando Rosell; Perkins, Gavin D.; Bossaert, Leo; Moertl, Maximilian; et al.
Abstract: Background: Survival after out-of-hospital cardiac arrest (OHCA) is still low. For every minute without resuscitation the likelihood of survival decreases. One critical step is initiation of immediate, high quality cardiopulmonary resuscitation (CPR). The aim of this subgroup analysis of data collected for the European Registry of Cardiac Arrest Study number 2 (EuReCa TWO) was to investigate the association between OHCA survival and two types of bystander CPR namely: chest compression only CPR (CConly) and CPR with chest compressions and ventilations (FullCPR). Method: In this subgroup analysis of EuReCa TWO, all patients who received bystander CPR were included. Outcomes were return of spontaneous circulation and survival to 30-days or hospital discharge. A multilevel binary logistic regression analysis with survival as the dependent variable was performed. Results: A total of 5884 patients were included in the analysis, varying between countries from 21 to 1444. Survival was 320 (8%) in the CConly group and 174 (13%) in the FullCPR group. After adjustment for age, sex, location, rhythm, cause, time to scene, witnessed collapse and country, patients who received FullCPR had a significantly higher survival rate when compared to those who received CConly (adjusted odds ration 1.46, 95% confidence interval 1.17–1.83). Conclusion: In this analysis, FullCPR was associated with higher survival compared to CConly. Guidelines should continue to emphasise the importance of compressions and ventilations during resuscitation for patients who suffer OHCA and CPR courses should continue to teach both.